Premiere showing of the film "Bernstein's Beethoven: Symphony no. 3" - Beethoven Society (New York):::Contributor::::::::::::; Bernstein, Leonard, 1918-1990:::Creator:::::::::::: (New York, NY; United States; Beethoven Society (New York), 2022)
Advertising handbill, autographed by Leonard Bernstein, for the premiere showing of his film "Bernstein's Beethoven: Symphony no. 3" with the Vienna Philharmonic, shown at the Metropolitan Museum of Art in New York.